2020
DOI: 10.34172/ps.2020.51
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia prostata Exerts Potent Anti-Inflammatory and Anti-Arthritic Activity in Downregulating the Increased Expression of Pro-Inflammatory Cytokines

Abstract: Background: Euphorbia prostrata constitutes a herbal medication widely used to cure numerous inflammatory diseases occurring either alone or in conjunction with other herbal formulations. The research conducted was devised with the aim of determining the effect of Euphorbia prostrata hydroalcoholic leaf extract on paw swelling, joint destruction, and the formation of inflammation-producing cytokines in animal models of rheumatoid arthritis. Methods: Hydroalcoholic Euphorbia prostrata extract and a reference dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, the earlier studies and yet these outcomes described here might suggest that all of the extracts used within the acetic-acid induced writhing experiment showed antinociceptive activity that might be attributed to inhibition through resident peritoneal cells contributes to the release of IL-1, IL-8 and TNFα [ 52 ]. A recent report also evidenced that aqueous-ethanolic crude extract of E. prostrata reduced the inflammation as well as oedema by inhibition proinflammatory cytokines modulating IL-1 via NF-κB dependent pathway [ 53 ] supporting its effect in regulation of immune response via reducing pain and augmenting phagocytic index.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the earlier studies and yet these outcomes described here might suggest that all of the extracts used within the acetic-acid induced writhing experiment showed antinociceptive activity that might be attributed to inhibition through resident peritoneal cells contributes to the release of IL-1, IL-8 and TNFα [ 52 ]. A recent report also evidenced that aqueous-ethanolic crude extract of E. prostrata reduced the inflammation as well as oedema by inhibition proinflammatory cytokines modulating IL-1 via NF-κB dependent pathway [ 53 ] supporting its effect in regulation of immune response via reducing pain and augmenting phagocytic index.…”
Section: Discussionmentioning
confidence: 98%
“…The constant stimulation of the brain's macrophages (microglia) may serve as a link in the progression of the pathogenesis of AD by exacerbating amyloid and tau proteins [34]. Some studies already revealed the anti-inflammatory potential of E. prostrata [35][36][37]. The consequences of the present study showed the significant anti-inflammatory potential of E. prostrata measured by the reduced level of inflammatory cytokines (IL-6 and TNF-α) in Scopolamine (1 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…A number of medicinal plants and their isolated compounds have been used to relieve arthritis for thousands of years (Gupta et al, 2020). Many plant-based constituents possess significant therapeutic values, such as downregulation of inflammatory channels, and are potential candidates for the treatment of arthritis (Hariyadi and Sahu, 2020). The presence of a number of phytochemicals belonging to the phenols, flavonoids, glycosides, coumarins, terpenoids, saponins, and fatty acid esters has been reported in S. sesuvioides by GC-MS analysis (Sajid-Ur- Rehman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%